Protection of Workers During Disasters: A Study in Light of the Saudi Labor Law - Aryam Munahi Thunayyan Albaqami (International Journal of Law Research and Studies, 2026)
This study examines the protection of workers during disasters in light of the Saudi legal system, particularly in view of the increasing forms of disasters worldwide and the diversity of their effects. The research problem lies in assessing the adequacy of the protection afforded by the Saudi legal system to workers in disaster situations, in terms of the preventive measures required before a disaster occurs, the procedures necessary during its occurrence, and the safeguards granted to workers after it has occurred, particularly with regard to the continuity of their rights and compensation for any harm they may sustain.The study adopts the analytical method to examine the relevant provisions of the Saudi Labor Law and its regulations, particularly the Occupational Safety and Health Management Regulation, in addition to the Social Insurance Law and the laws and regulations related to safety requirements. It also draws on the descriptive method in presenting the concept of disasters, their forms, and their effects on workers and the employment relationship.The study reached several findings, most notably that the protection of workers during disasters is not governed by a standalone legal framework, but is derived from various provisions scattered across the Labor Law and its regulations, the Social Insurance Law, and the laws and regulations related to safety requirements. The study also concluded that this protection is based on interconnected stages, beginning with risk prevention before the occurrence of a disaster, followed by the protection of workers’ safety and rights during the disaster, and ending with subsequent protection through the prescribed compensation where the injury arising from the disaster is connected to the employment relationship and falls within the scope of work injuries.The study further concluded with several recommendations, most notably that the Saudi regulator should issue a regulation or regulatory provisions on occupational safety and health management for facilities employing fewer than fifty workers, in order to ensure a minimum level of preventive measures and emergency plans appropriate to the nature of such facilities.
Keywords: Disasters; Worker Protection; Occupational Safety and Health; Work Injuries; Force Majeure; Employment Contract; Saudi Labor Law